University Cafeterias and Dining Halls and Their Relationship with Dietary Habits, Perceptions, and Student Well-being - Delgado Cabrera, Freddy Walter (2025)
The transition to university life is often accompanied by changes in diet and lifestyle, which can lead to imbalances in eating practices. In this way, institutional food environments shape and influence the daily dietary behaviors of the university population. This study aimed to analyze the relationship between eating habits, perceptions, and well-being among university students based on their consumption in cafeterias and dining halls. A structured questionnaire was used, consisting of four sections that included sociodemographic data, eating habits, dietary choices, and subjective well-being. The results showed that 48.4 % of students consume food in cafeterias or dining halls five or more times per week, with a mean healthy consumption index (ISA_A = 35.3) higher than that of ultra-processed foods (ISA_B = 23.0). The average weekly expenditure was 17.5 soles, with significant differences between universities (p = 0.0059). Furthermore, a positive correlation was observed between healthy food consumption and subjective well-being (r = 0.42; p < 0.001), as well as between physical activity and perceived health (r = 0.37; p < 0.01). In conclusion, universities should promote healthy food environments, adequate rest, and regular physical activity.